\[\lim_{x \rightarrow \infty}x_{n} = 0.\]
\[1)\ x_{n} = \frac{1}{n + 1}:\]
\[\lim_{x \rightarrow \infty}\frac{1}{n + 1} = \lim_{x \rightarrow \infty}\frac{\frac{1}{n}}{1 + \frac{1}{n}} =\]
\[= \frac{0}{1 + 0} = 0.\]
\[Что\ и\ требовалось\ доказать.\]
\[2)\ x_{n} = \frac{1}{\sqrt[3]{n}}:\]
\[\lim_{x \rightarrow \infty}\frac{1}{\sqrt[3]{n}} = \lim_{x \rightarrow \infty}\left( \frac{1}{n} \right)^{\frac{1}{3}} = 0.\]
\[Что\ и\ требовалось\ доказать.\]
\[3)\ x_{n} = \frac{1}{n^{3}}:\]
\[\lim_{x \rightarrow \infty}\frac{1}{n^{3}} = \lim_{x \rightarrow \infty}\left( \frac{1}{n} \right)^{3} = 0.\]
\[Что\ и\ требовалось\ доказать.\]
\[4)\ x_{n} = \frac{1}{2^{n}}:\]
\[\lim_{x \rightarrow \infty}\frac{1}{2^{n}} = \lim_{x \rightarrow \infty}\left( \frac{1}{2} \right)^{n} = 0.\]
\[Что\ и\ требовалось\ доказать.\]
\[5)\ x_{n} = \frac{1}{3n + 2}:\]
\[\lim_{x \rightarrow \infty}\frac{1}{3n + 2} = \lim_{x \rightarrow \infty}\frac{\frac{1}{n}}{3 + \frac{2}{n}} =\]
\[= \frac{0}{3 + 0} = 0.\]
\[Что\ и\ требовалось\ доказать.\]
\[6)\ x_{n} = \frac{n + 1}{n^{2}}:\]
\[\lim_{x \rightarrow \infty}\frac{n + 1}{n^{2}} = \lim_{x \rightarrow \infty}\left( \frac{1}{n} + \frac{1}{n^{2}} \right) =\]
\[= 0 + 0 = 0.\]
\[Что\ и\ требовалось\ доказать.\]